Memahami Identifikasi Hukum Bacaan Tajwid melalui Permainan Samudra Tajwid di Pendidikan Diniyah Formal Wustha Zainul Hasan Genggong - Maghfiro; Kustiana Arisanti; Ummi Laila Maghfiro (Irfani, 2026)
This research aims to develop a valid, practical, and effective "Samudra Tajwid" game media to bridge the gap between theoretical understanding and the practical ability of students in identifying the laws of tajweed reading. Using the development research method with the ADDIE model, this research was carried out at the Wustha Zainul Hasan Genggog Formal Early Education (PDF), Probolinggo, with 15 Wustha class II students who were selected purposively. Data were collected through structured interviews, Likert scale questionnaires, and documentation, which were then analyzed using qualitative and quantitative descriptive approaches. The results of the study showed that Samudra Tajwid media met the very high academic eligibility criteria based on the assessment of media experts (92.8%), material experts (94.4%), and linguists (93.7%). The level of media practicality is also in the very practical category according to the responses of educators (95%) and students (91.6%). The impact of implementation in the classroom proves the effectiveness of media with an increase in affective, social, and the highest improvement in the cognitive domain. The conclusion of this research confirms that the integration of educational-creative elements is able to reform the monotonous conventional classroom atmosphere into a dynamic student-centered learning ecosystem through a peer tutoring mechanism. The practical implications of these findings show that the methodological renewal of tajweed teaching in Islamic boarding schools can be optimally accelerated without having to remove the substance of the local book curriculum, but by reconstructing learning media that is adaptive to the psychosocial characteristics of adolescents